System-Level Retiming and Pipelining - Venkataramani, Girish; Yongfeng Gu (2014 IEEE 22nd Annual International Symposium on Field-Programmable Custom Computing Machines, 2014)
In this paper, we examine retiming and pipelining in the context of system-level optimization techniques. Our main contributions are: (a) functionally equivalent retiming and delay balancing as necessary techniques for pipelining and retiming system-level graphs while maintaining numerical fidelity, and (b) clock-rate pipelining, as a new technique that leverages the knowledge of multi-rate design spec to pipeline multi-cycle paths. All these techniques have been implemented within HDL Coder™, a tool that generates synthesizable HDL code from Simulink ® and MATLAB®.